Methodology of social control of projects to improve the supervision of public works - Calderón Paniagua, Dennys Geovani (2021)
The main objective of this research was to design a methodology for the social control of projects to improve the supervision of public works in the entities of the Peruvian state. This research was of an applied type, it also had an explanatory level design, since it generated and evaluated the adequate implementation of the process flow chart proposed in the proposed methodology, it also had a non-experimental research design. Regarding the population, it was made up of public entities of the Peruvian state with the capacity to carry out public works, also in the present case the sample was made up at random, by a public entity that executes works in the Tacna region. As results of the research, the procedures and formats were designed based on the process flow chart that contemplates the methodology of social control of projects, which after its application, demonstrated to improve the supervision of public works in a public entity in the Tacna region. The conclusion is that it has been possible to develop a methodology for social control of projects, which improved the supervision of public works, evidencing situations of non-compliance in a public entity in the Tacna region.